Aseptic (avascular) bone necrosis in the foot and ankle - Martin Oliva, Xavier (EFORT Open Rev, 2020)
Aseptic necrosis may be defined as a group of diseases that have bone necrosis as a common denominator. They usually appear in the epiphyses and in the carpal and tarsal bones. They generally appear during a growth period and principally at those skeletal points subjected to particular stress. In Müller–Weiss disease in the advanced stages, talonavicular-cuneiform arthrodesis, with or without back foot correction, is the best surgical option. In Freiberg–Kohler disease, treatment can be conservative and we can maintain the head of the metatarsal by performing a joint debridement of the metatarsophalangeal joint with removal of loose bodies. The lateral upper and lower faces of the distal extremity of the metatarsal are resected, preserving the joint cartilage that in its centre portion is always healthy. The osteophyte border that may be present in the phalanx is resected. Most frequently, avascular necrosis (AVN) of the talus is a sequel to talar fractures, with the possibility that the AVN increases with the severity of the trauma and the damage associated with the already precarious blood supply of the talus. The surgical treatment used for sesamoid AVN is partial excision of the affected bone. Cite this article: EFORT Open Rev 2020;5:684-690. DOI: 10.1302/2058-5241.5.200007